Probabilidade condicional: um enfoque de seu ensino-aprendizagem - Figueiredo, Auriluci de Carvalho (2000)
This work has for objective to introduce the concept of the Conditional Probability in courses of Statistics in the University. For that we elaborated, we applied and we analyzed the results of a teaching sequence taking in consideration the beginnings of a Didactic Engineering. This teaching sequence is composed of four activities that they were created, basing on Carmen Batanero's didactic situations and other, with the aim of doing the student to contemplate on circumstances that involve not only the Conditional Probability, as the concepts linked to the Theorem of the Total Probability and the Theorem of Bayes. To work with such concepts we articulated in the subjects of the activities different representation registrations: natural, symbolic language, diagram of trees and contingency table, taking as base the Theory of Registrations of Representation of Raymond Duval. We applied this sequence to students of the courses of Licentiate of Mathematics and Science of the Computation and before the those students' protocols, we concluded that our sequence aided them they decrease it the difficulties lifted by us and for the researchers and at the same time it indicated themes for future researches in the area. Enter other conclusions stood out that most of the students before subjects that involve the Conditional Probability differentiated this of the Probability of the intersection of events and I calculate it of P(A/B) of the one of P(B/A), since these if they come in the questions in natural language. However when similar subjects were presented in the language symbolic many students they showed difficulties in solving them